2014
DOI: 10.1002/bjs.9651
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of high-versuslow-chloride content in perioperative and critical care fluid resuscitation

Abstract: BackgroundThe objective of this systematic review and meta-analysis was to assess the relationship between the chloride content of intravenous resuscitation fluids and patient outcomes in the perioperative or intensive care setting.MethodsSystematic searches were performed of PubMed/MEDLINE, Embase and Cochrane Library (CENTRAL) databases in accordance with PRISMA guidelines. Randomized clinical trials, controlled clinical trials and observational studies were included if they compared outcomes in acutely ill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
182
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(199 citation statements)
references
References 75 publications
6
182
0
11
Order By: Relevance
“…However, there is currently no real randomized controlled trial that confirms these data and results concerning mortality remain uncertain [82,85]. A recent meta-analysis including more than 6000 patients concluded that the use of crystalloids rich in chloride increases the risk of AKI and blood transfusion, without affecting mortality rates as compared with balanced solutions [86]. Finally, considering these data, we consider non-balanced solutions as potentially deleterious, especially for kidneys, and suggest minimizing their use, especially for large-volume resuscitation [87].…”
Section: (Grade 2+) Strong Agreementmentioning
confidence: 99%
“…However, there is currently no real randomized controlled trial that confirms these data and results concerning mortality remain uncertain [82,85]. A recent meta-analysis including more than 6000 patients concluded that the use of crystalloids rich in chloride increases the risk of AKI and blood transfusion, without affecting mortality rates as compared with balanced solutions [86]. Finally, considering these data, we consider non-balanced solutions as potentially deleterious, especially for kidneys, and suggest minimizing their use, especially for large-volume resuscitation [87].…”
Section: (Grade 2+) Strong Agreementmentioning
confidence: 99%
“…The most commonly used crystalloid solution globally is 0.9% sodium chloride (saline) (2), with more than 200 million liters administered each year in the United States alone (1). However, the high chloride content of saline has been hypothesized to contribute to the development of acute kidney injury (AKI) in at-risk patients (3,4). Alternatives to saline include crystalloids with electrolyte compositions that more closely approximate that of plasma (balanced crystalloids), such as lactated Ringer's solution or Plasma-Lyte A.…”
mentioning
confidence: 99%
“…Alternatives to saline include crystalloids with electrolyte compositions that more closely approximate that of plasma (balanced crystalloids), such as lactated Ringer's solution or Plasma-Lyte A. Emerging data suggest that the use of balanced crystalloids in critically ill adults may decrease rates of AKI (3,4), renal replacement therapy (RRT) (3,5), and death (6,7).…”
mentioning
confidence: 99%
“…Toxicity, in general, is dose dependent and the consequences of the exposure depend on the susceptibility of the patients, as for all the other substances present in nature, water included (18). Serum chloride concentrations were not reported in the study by Young and colleagues (6). Therefore, it could be argued that the negative (mainly renal) effects of chloride loading might be more pronounced, and therefore easier to be demonstrated, in sicker patients, with more limited renal functional reserve, who receive larger chloride amounts with replacement fluids.…”
mentioning
confidence: 95%
“…With this background, safety concerns arose about the use of saline in critically ill patients and other nonrandomized studies and meta-analyses seemed to confirm that high chloride content of saline may contribute to the development of acute kidney injury (AKI), increase the need for RRT, and even rise the mortality rate (6,7). In light of these effects on renal function, balanced solutions with lower, more physiologic chloride concentration, have been suggested (1,4 .…”
mentioning
confidence: 99%